Pengaruh Komunikasi Dan Kreativitas Terhadap Kinerja Aparatur Desa Di Kecamatan Nita Kabupaten Sikka (Studi Kasus Pada Desa Nita, Desa Nitakloang, Desa Tebuk Dan Desa Lusitada) - Stevania Dua Mahing; Imanuel Wellem; Kristiana Reinildis (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aimed to (1) graps the representation of official performance, communication, and creativity, (2) analyze the effect of communication and creativity on official performance both partially or simultaneously. The population in this study was the official village of Nita Sub-district, Sikka Regency with a total of 36 people and done by census or saturated sampling. Data were collected through questioner and then analyzed by descriptive and statistical inferential methods such as multiple regression linear. The hypothesis was done thourgh F-test and T-test.The descriptive analysis showed that the variables of official performance, communication, and creativity were categorized as good. The result of the statistic T-test showed that partially the variable of communication and creativity had a positive impact on the village administration’s performance. The result of the statistical F test showed that simultaneously, the variables of communication and creativity had a significant influence on the village administration’s performance. The result of the determination showed that both independent variables in this study were able to enlighten the fluctuation of village administration’s performance at Nita Sub-district of Sikka Regency by 31%.